Dequantization of electric charge: Probing scenarios of cosmological multi-component dark matter - Duong Van Loi; Nguyen Manh Duc; Phung Van Dong (Nuclear Physics B, 2022)
Since the electric charge in the standard model is theoretically not quantized, we may have a variant of it, called dark charge. Similar to the electric charge, the dark charge neither commutes nor closes algebraically with SU(2)L. The condition of algebraic closure leads to a novel gauge extension, SU(2)L⊗U(1)Y⊗U(1)N, where Y and N determine the electric and dark charges, respectively, apart from the color group. We argue that the existence of the dark charge, thus N, leads to novel scenarios of multi-component dark matter, in general. The dark matter stability is determined by a residual (or dark charge) gauge symmetry isomorphic to an even Zk discrete group, where k is specified dependent on the value of the neutrino dark charge. This residual symmetry divides the standard model particles into distinct classes, which possibly accommodate dark matter, but each dark matter candidate cannot decay due to the color and electric charge conservation. We analyze in detail three specific models according to k=2,4,6 and determine the simplest dark matter candidates. For small U(1)N coupling, the two-component dark matter scenarios implied by the dark charge successfully explain the dark matter relic density and the recent XENON1T excess, as well as the beam dump, neutrino scattering, and astrophysical bounds. Otherwise, for large U(1)N coupling, we have multi-WIMPs coexisted beyond the weak scale.